Implementation of a university faculty mentorship program - Foxcroft, Laura; Jones, Douglas; Steele, Margaret; Lim, Rodrick (Canadian Medical Education Journal, 2018)
Objective: To implement a University Faculty mentorship program in the Division of Emergency Medicine. Methods: A program based on a unique Schulich faculty mentorship policy was implemented with the help of a Provider Value Officer. The process involved creating a training program which defined the roles of the mentors and mentees and established the principles of an effective mentor-mentee relationship. Faculty received training on how to participate effectively in a Schulich faculty mentorship committee. Each committee consisted of a mentee, and two mentors at the associate professor level (one internal and one external) . Thirteen distinct external divisions were represented. They were instructed to meet twice per year, as arranged by the mentee. The mentee created mentor minutes using a template, and then submitted the minutes to the members of the mentorship committee and the Chair/Chief of Emergency medicine. The Chair/Chief used the minutes during the annual Continuing Professional Development meeting. Results: In less than a year, the division has successfully transformed its mentorship program. Using the above-mentioned process, 31 of 34 (91%) eligible assistant professors have functioning mentorship committees. Collaboration and participation between the different faculties has increased. Follow-up meetings with the Chair/Chief and the Provider Value Officer revealed the theme that, universally, participants have perceived Schulich Faculty Mentorship committees as beneficial and are happy with the "fit" of their mentorship committees. Conclusion: Through careful planning and training, a successful Faculty Mentorship program can be initiated in an academic division in less than a year with the help of a local champion given protected time.